Analisis Produktivitas Menggunakan Metode POSPAC dan Performance Prism Sebagai Upaya Peningkatan Kinerja (Studi Kasus: Industri Baja Tulangan di PT. X Surabaya) - Rony Prabowo; Rizal Aditia (Jurnal Rekayasa Sistem Industri, 2020)
This study aims to identify the partial productivity index and performance measurement in order to make efforts to increase the productivity of the production section at PT. X Surayaba which produces reinforcing steel using a rolling mill with POSPAC method and Performance Prism. Through productivity measurement POSPAC method obtained fluctuating results every month in each indicator the highest productivity ratio in the labor indicator in the July period with a productivity ratio of 76.96 and a productivity index of 123%, for the measurement of the lowest productivity in the product indicator the value of the productivity ratio of 0.61 and the productivity index of 87%. Through the Performance Prism method it is known that labor indicators need to be improved because based on KPI values only get a value of 29% due to low disciplinary factors and less effective at work. Keywords: productivity, production, performance, prism, effective